An Identity with Skew Derivations on Lie Ideals (Communications in Mathematical Research, 2021)
Let $R$ be a 2-torsion free prime ring and $L$ a noncommutative Lie idealof $R$. Suppose that $(d, σ)$ is a skew derivation of $R$ such that $x^sd(x)x^t = 0$ for all $x ∈ L$, where $s, t$ are fixed non-negative integers. Then $d = 0$.
Keywords: skew derivation; generalized polynomial identity; Lie ideal; prime ring.